Analisis Faktor - Faktor Yang Mempengaruhi Return On Investment (ROI) Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Periode 2018-2020 - Putri Rotua Jaya Br Sipayung; Nisma Apriyani Hulu (Owner : Riset dan Jurnal Akuntansi, 2022)
This study aims to see how a relationship individually or simultaneously with the title Analysis of Factors Affecting Return On Investment (ROI) in Manufacturing Companies Listed on the Indonesia Stock Exchange (2018-2020). The factors studied are Sales Variables (X1), Operating Costs (X2), Cash Turn Over (X3) and Inventory Turnover Variables (X4). This research observation uses purposive sampling with partial test (T test), simultaneous test (F test), classical assumption test, and Adjusted R square test. The test results for this observation are (1) the Sales variable has no effect on Return On Investment. (2) Operating Cost Variable Affects Return On Investment (3) Cash Turn Over variable has an effect but not significant on Return On Investment. (4) the inventory turnover variable has an effect but is not significant on the Return On Investment. (5) Sales Variables, Operating Costs, Cash Turn Over, and Inventory Turnover Variables have a Simultaneous effect on the Return On Investment Variable. With the results of Adjusted R square of 0.277 (27.7%) and influenced by other variables of 76.3%. So the overall results of Sales, Operating Costs, Cash Turn Over, and Inventory Turnover have a simultaneous effect on Return On Investment in Manufacturing Companies Listed on the Indonesia Stock Exchange